Somatic mutation landscape of a meningioma and its pulmonary metastasis - Yaran Du; Ting Lu; Song Huang; Fangfang Ren; Gang Cui; Jian Chen (Cancer Communications, 2018)
Abstract Background Extracranial metastasis (ENM) of meningiomas is extremely rare, and typically occurs several years after a primary tumor is diagnosed. However, the genetic changes underlying ENM events have not yet been investigated. Case presentation A 58-year-old male patient was sent to the emergency room of our hospital because of a sudden fall. Magnetic resonance imaging detected a mass at the right frontal sagittal sinus. He underwent tumor resection and recovered well, but post-operative computed tomography revealed three lumps on the right side of his chest. Thoracic surgery was performed to remove two of the lumps. Pathological findings revealed that the brain and lung tumors were grade I meningiomas. The patient received no additional radiation or chemotherapy post-surgery, and there was no sign of tumor recurrence in the brain or progression of the remaining lump in the chest 1 year after surgery. We performed whole exome sequencing of the patient’s blood, primary brain tumor, and lung metastatic tumor tissues to identify somatic genetic alterations that had occurred during ENM. This revealed that a frameshift deletion of the neurofibromin 2 gene likely drove formation of the meningioma. Surprisingly, we found that the brain tumor was relatively homogeneous and contained only one dominant clone; both the pulmonary metastasis and the original brain tumor were derived from the same clone, and no obvious additional driver mutations were detected in the metastatic tumor. Conclusion Although ENM of meningiomas is very rare, brain tumor cells appear to be more adaptable to tissue microenvironments outside of the central nervous system than was commonly thought.